Assessment and Treatment Considerations for Post Traumatic Stress Disorder at End of Life. (August 2018) - Glick, Debra M.; Cook, Joan M.; Moye, Jennifer; Kaiser, Anica Pless
Post traumatic stress disorder (PTSD) may first emerge, reemerge, or worsen as individuals approach end of life and may complicate the dying process. Unfortunately, lack of awareness of the occurrence and/or manifestation of PTSD at end of life can lead to PTSD going unaddressed. Even if PTSD is properly diagnosed, traditional evidence-based trauma-focused treatments may not be feasible or advisable with this group as many patients at end of life often lack the physical and mental stamina to participate in traditional psychotherapy. This article reviews the clinical and empirical literature on PTSD at end of life, as well as discusses assessment and psychotherapy treatment issues with this neglected population. In addition, it expands on the current reviews of this literature 1–3 by extrapolating results from nontraditional treatment approaches with other patient populations. Elements of these approaches with patients sharing similar characteristics and/or comorbidities with patients with PTSD at end of life may provide additional benefits for the latter population. Clinical implications and suggestions for interdisciplinary care providers are provided.